Fabrication of nanofiber coated with l-arginine via electrospinning technique: a novel nanomatrix to counter oxidative stress under crosstalk of co-cultured fibroblasts and satellite cells. (1st January 2018) - Allur Subramaniyan, Sivakumar; Sheet, Sunirmal; Balasubramaniam, Saravanakumar; Berwin Singh, Swami Vetha; Rampa, Dileep Reddy; Shanmugam, Sureshkumar; Kang, Da Rae; Choe, Ho Sung; Shim, Kwan Seob
Abstract: The objective of this study was to synthesize and characterize novel polyurethane (PU)-nanofiber coated withl -arginine by electrospinning technique. This study determined whetherl -arginine conjugated with PU-nanofiber could stimulate cell proliferation and prevent H2 O2 -induced cell death in satellite cells co-cultured with fibroblasts isolated from Hanwoo (Korean native cattle). Our results showed thatl -arginine conjugated with PU nanofiber could reduce cytotoxicity of co-cultured satellite cells. Protein expression levels of bcl-2 were significantly upregulated whereas those of caspase-3 and caspase-7 were significantly downregulated in co-culture of satellite cells compared to those of monoculture cells after treatment with PU-nanofiber coated withl -arginine and which confirmed by Confocal microscope. These results suggest that co-culture of satellite cells with fibroblasts might be able to counter oxidative stress through translocation/penetration of antioxidant, collagen, and molecules secreted to satellite cells. Therefore, this nanofiber might be useful as a wound dressing in animals to counter oxidative stresses.